2015
DOI: 10.1111/ssqu.12198
|View full text |Cite
|
Sign up to set email alerts
|

Economic Inequality and Nonviolent Protest*

Abstract: Objective. Despite substantial theorizing, the relationship between economic inequality and participation in nonviolent protests has not been satisfactorily examined empirically. Methods. Using multilevel models of data from four waves of the European Social Survey, this article examines whether differences in inequality across countries and over time help explain people's engagement in peaceful protest. Results. It finds that greater inequality reduces protest participation for all those with incomes below th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 26 publications
(35 reference statements)
2
77
0
1
Order By: Relevance
“…In addition, marital status has been found to be more strongly associated with political behaviors and perceptions of political behaviors than political attitudes. In addition, married people have reported less participation even for nonviolent and lawful protests (Solt, 2015). The data from World Values Surveys of 37,716 citizens in 17 more advanced democratic countries further showed that during social movements, married people tended to sign petitions to express their stances, whereas unmarried people tended to take part in demonstrations directly (Dodson, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, marital status has been found to be more strongly associated with political behaviors and perceptions of political behaviors than political attitudes. In addition, married people have reported less participation even for nonviolent and lawful protests (Solt, 2015). The data from World Values Surveys of 37,716 citizens in 17 more advanced democratic countries further showed that during social movements, married people tended to sign petitions to express their stances, whereas unmarried people tended to take part in demonstrations directly (Dodson, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The idea that social unrest evolves as a reaction to injustice and widespread deprivation figured prominently in traditional Marxian theories on protest and revolution. During the recent economic crisis, however, this link has again gained momentum: the simultaneous occurrence of a widespread increase in economic hardship and the impressive surge in unconventional political mobilisation renewed the scholarly interest in grievance theory and triggered new empirical evaluation on economic determinants of political protest (Bernburg 2015;Della Porta 2015;Giugni & Grasso 2015;Grasso & Giugni 2016;Kern et al 2015;Rüdig & Karyotis 2014;Solt 2015). However, the relative deprivation approach largely failed to prove its explanatory power in empirical work, as there did not seem to be a direct link between (relative) deprivation and protest behavior, and increasingly fell out of fashion (Gurney & Tierney 1982).…”
Section: Economic Grievances and Participation In The Literaturementioning
confidence: 99%
“…In the 1940s and 1950s, the theory has been refined insofar as the focus shifted from deprivation in absolute terms to relative deprivation -that is, unmet expectations (see, e.g., Geschwender 1964;Gurr 1970;Runciman 1966). Nevertheless, this more recent empirical work does not conclusively answer whether economic hardship mobilises or de-mobilises citizens: single-country studies as well as comparative evaluations come to diverging conclusions regarding the impact of grievances on protest activity (see, e.g., Bernburg (2015) on Iceland; Rüdig & Karyotis (2014) on Greece; or Solt (2015) for a comparative study). During the recent economic crisis, however, this link has again gained momentum: the simultaneous occurrence of a widespread increase in economic hardship and the impressive surge in unconventional political mobilisation renewed the scholarly interest in grievance theory and triggered new empirical evaluation on economic determinants of political protest (Bernburg 2015;Della Porta 2015;Giugni & Grasso 2015;Grasso & Giugni 2016;Kern et al 2015;Rüdig & Karyotis 2014;Solt 2015).…”
Section: Economic Grievances and Participation In The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Karakoç (2013) finds that people of all incomes belong to fewer civil-society associations where inequality is greater. Solt (2015) documents that, where inequality is higher, participation 1 Yet a third theoretical perspective contends that the more divergent material conditions of richer and poorer citizens in contexts of higher inequality will spark more contentious-and therefore more interestingpolitics and so coincide with greater rates of participation across all income levels (see Brady 2004). This conflict theory, however, has not received much, if any, empirical support in prior research (see, e.g., Solt et al 2016Solt et al , 2017.…”
mentioning
confidence: 99%